Utilizing Blockchain Technology in the Pharmaceutical Enterprise Business - Venkata Pavan Kumar Juturi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Blockchain technology is propelling the digital evolution across multiple sectors, with the pharmaceutical industry emerging as a beneficiary of this transformative innovation. This sector faces obstacles such as opacity, product tracking complexities, trust deficits, and challenges in managing expired shipments. To tackle these issues, blockchain technology has been leveraged as a remedy. Counterfeit drug prevention stands out as a predominant focus, reflecting the pharmaceutical industry’s key priority. Blockchain technology, an emerging innovation, is gaining traction across various sectors, including healthcare. Within healthcare, Blockchain networks are being deployed to securely manage and exchange patient data among hospitals, diagnostic labs, pharmacies, and healthcare professionals. These Blockchain applications play a vital role in identifying and mitigating critical errors, potentially hazardous ones included, within healthcare practices. Consequently, this technology holds potential for enhancing the efficiency, security, and transparency of medical data sharing within the healthcare system. Additionally, it furnishes valuable tools for medical institutions to glean insights and enhance the analysis of medical records. It visually illustrates the wide-ranging capabilities, facilitators, and cohesive workflow of Blockchain technology in bolstering global healthcare. Furthermore, the paper provides an in-depth examination of fourteen notable applications of Blockchain technology in healthcare, emphasizing its crucial role in tackling challenges such as fraudulent practices within clinical trials. Blockchain’s potential in healthcare lies in improving data efficiency, assuaging concerns about data manipulation, and establishing a robust data storage framework with the highest level of security. It provides functionalities including adaptability, connectivity, accountability, and verification for accessing data. Safeguarding the privacy and integrity of medical records is paramount, and Blockchain enables decentralized data security in healthcare, thus reducing certain risks.